Correlation of microstructure, pore characteristics and hydration properties of wheat bran modified by airflow impact mill. (May 2022) - Li, Yang; Wang, Lijuan; Wang, Haoran; Li, Zaigui; Qiu, Ju; Wang, Lili
Abstract: Strategies that could modify the structure of wheat bran by micronization are of great interest to improve its industrial application. The correlation between microstructure, pore characteristics and hydration properties of plant-scale, tissue-scale and cellular-scale wheat bran modified by airflow impact mill (AFIM) was investigated. AFIM treatment mainly caused different structural disruption of micropores in pericarp and aleurone layer, which significantly increased the soluble dietary fiber content, water-soluble index, whiteness and suspension stability of AFIM-treated wheat bran, but had a negative effect on its hydration properties (including water retention capacity, swelling capacity and oil retention capacity). Pearson correlation analysis indicated that the water retention capacity of wheat bran was significantly correlated with the percentage of microporous at the cellular level ( r  = − 0.99) and the tissue level ( r  = 0.72). These results could guide the application of different scales wheat bran in food systems. Highlights: AFIM treatment could destroy the tissue and cell structure of wheat bran. AFIM treatment caused the redistribution of wheat bran micropores. WRC of tissue-level micropore was stronger than that of cellular-level micropore. Superfine wheat bran showed apparently better suspension stability.